Inhibitory effect of 17β-estradiol on the THIK-1 channel - Michihiro Tateyama; Yoshihiro Kubo (PLoS ONE, 2026)
A two-pore domain K + (K2P) channel, THIK-1, plays important roles in microglia and macrophage. THIK-1 is known to be activated by arachidonic acid and G protein-coupled receptors and inhibited by anesthetics. Steroids, such as cholesterol, estradiol and progesterone, are known to modulate several K + channels and they might be potential modulators of THIK-1. We examined the effects of steroids on THIK-1 and found that estradiol inhibits mouse THIK-1 by approximately 40% (IC 50 = 4.9 ± 1.5 μM). Docking simulations of THIK-1 with estradiol indicated possible docking sites, which were further assessed by introducing an alanine mutation into a residue at or near these locations. The F142A, V269A, and Y273A mutations reduced the inhibitory effect of estradiol. These residues are situated within the upper cavity above the Y gate in THIK-1 (pond), suggesting that the pond conformation is essential for estradiol-mediated inhibition. Conversely, the F145A and F276A mutations, located outside this region, were inhibited by 10 nM estradiol and enhanced inhibition by estradiol, estrone, estriol, and progesterone, likely due to conformational changes that facilitate steroid inhibition. The mouse T237S mutation, which corresponds to the reported human THIK-1 variant, produced effects similar to those seen with the F145A and F276A mutations, but to a lesser degree. In summary, estradiol-mediated THIK-1 inhibition depends on residues located in the pond, which may have physiological or pathological significance for THIK-1 variants which are inhibited by low concentration of estradiol.